2003
DOI: 10.1890/02-5086
|View full text |Cite
|
Sign up to set email alerts
|

The Pace of Ecosystem Development of Constructed Spartina Alterniflora Marshes

Abstract: Abstract. Ecological attributes were measured along a chronosequence of 1-to 28-yrold, constructed Spartina alternifIora marshes to identify trajectories and rates of ecosystem development of wetland structure and function. Attributes related to biological productivity and diversity (Spartina, epiphytic and sediment algae, benthic invertebrates), soil development (sediment deposition, organic C, N, P, organic matter quality), and microbial processes (C mineralization) were compared among e i a t constructed ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
184
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(206 citation statements)
references
References 42 publications
18
184
2
Order By: Relevance
“…~c c o m~a n~i n g changes in the rate of detritus processing provide plausible measures of ecosystem function. A number of studies have confirmed that benthic organic matter accumulates, at least initially, in some created wetlands, and that natural wetland substrate has a higher organic content and a lower density than that of young created wetlands (Craft et al 1999and 2003, Zedler and Callaway 1999, Nair et al 2001. Further, there is evidence that the rates of detritus decomposition (Atkinson and Cairns 2001) and carbon mineralization (Craft et al 2003) increase with age in created wetlands.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…~c c o m~a n~i n g changes in the rate of detritus processing provide plausible measures of ecosystem function. A number of studies have confirmed that benthic organic matter accumulates, at least initially, in some created wetlands, and that natural wetland substrate has a higher organic content and a lower density than that of young created wetlands (Craft et al 1999and 2003, Zedler and Callaway 1999, Nair et al 2001. Further, there is evidence that the rates of detritus decomposition (Atkinson and Cairns 2001) and carbon mineralization (Craft et al 2003) increase with age in created wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have confirmed that benthic organic matter accumulates, at least initially, in some created wetlands, and that natural wetland substrate has a higher organic content and a lower density than that of young created wetlands (Craft et al 1999and 2003, Zedler and Callaway 1999, Nair et al 2001. Further, there is evidence that the rates of detritus decomposition (Atkinson and Cairns 2001) and carbon mineralization (Craft et al 2003) increase with age in created wetlands. Decomposition dynamics have important associations with wetland soil development, seed germination, faunal colonization, and hydrologic regime Callaway 1999, Taylor andMiddleton 2004), and as such they may be suitable tools for assessing the evolution of ecosystem function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coastal marshes have been managed for forage and grazing for centuries (Gedan et al 2009), and they are increasingly under heavy pressure from human development including pollution, introduced species, altered hydrology (including nutrient and sediment loadings), and climate change (Adam 2002;Scavia et al 2002;Kirwan and Megonigal 2013). Many have been degraded and even destroyed by direct and indirect human management on the Atlantic (Coverdale et al 2014;Kearney et al 2002), Gulf (Turner 2011), and Pacific coasts (Craft et al 2003;Kennish 2001). Kirwan et al (2010) summarized the stability of coastal marshes as the balance between accretion and submergence where biological and physical factors interact to modify the marsh environment.…”
Section: Soil Change In Wetlandsmentioning
confidence: 99%
“…We refrain from calling the SWAMP a fully restored wetland since reverting to the original state (Bradshaw, 1996) is an unattainable goal after only a few years (Craft et al, 2003). Instead, the SWAMP is a designed wetland complex that includes riverine, palustrine, and lacustrine wetlands to maximize habitat for biota as well as improve water quality.…”
Section: Introductionmentioning
confidence: 99%